Effectiveness of Technology-Integrated Instruction in Improving Mathematics Achievement - Dahal, Prem Prasad (THE ACADEMIA, 2026)
Mathematics is one of the fundamental subjects that form the basis of problem solving, scientific thinking and technological innovation, however, traditional teaching practices are not always conducive to students to engage and achieve. This study aimed to compare the effectiveness of ICT based instructional methods with traditional teaching methods on the mathematics achievement of students at the secondary level and to check if there existed any difference in gender in both instructional settings. A quantitative method of research was used in the form of quasi-experimental pre-test post-test non-equivalent control group design. 346 students from grade Nine were selected as sample from three secondary schools in Bhaktapur District and from them: the experimental group of the experimental class was taught with the ICT tools i.e. GeoGebra and the control group of the control class was taught by using the conventional teaching method. Data were collected using a validated 40 item objective achievement test based on Bloom's Taxonomy and the reliability of the test was checked using the split half method (r = 0.78). Statistical analyses, including descriptive statistics and independent samples t-tests were used to find group differences at 0.05 level of significance. Results showed no significant difference in the pre-test scores between the two groups while results of the post-test scores showed that the experimental group had a significant increase in scores compared with the control group. However, significant gender differences were also found in the post-test in both instructional conditions, and male students had better results than female students. The conclusion of the study is that the ICT integrated instruction is more effective than traditional method in improving mathematics achievement while there are persistent gender disparities which demonstrate a need for a targeted strategy to better support the female learners in technology-enhanced mathematics classrooms.